The expression of cuproptosis-related genes in hepatocellular carcinoma and their relationships with prognosis - Zhao, Xueying; Chen, Jin; Yin, Shangqi; Shi, Jingren; Zheng, Mei; He, Chaonan; Meng, Huan; Han, Ying; Han, Jinyu; Guo, Jingjing; Yuan, Zhengrong; Wang, Yajie (Frontiers in Oncology, 2022)
Background: The mechanism of cuproptosis has recently been reported to lipoylated proteins in the tricarboxylic acid (TCA) cycle. Besides, the role of copper was previously recognized in cancer progression. We evaluated the prognostic value of cuproptosis-related gene expression in hepatocellular carcinoma (HCC). Methods: Remarkable genes were selected both in differential expression analysis and Kaplan-Meier survival analysis from ninety-six cuproptosis-related genes using The Cancer Genome Atlas (TCGA) database. The relationships between clinical characteristics and gene expression were performed with Wilcoxon signed-rank test, Kruskal-Wallis test, and logistic regression. Clinicopathologic factors correlated with overall survival in HCCs conducting univariate and multivariate Cox regression analysis. Gene Expression Profiling Interactive Analysis 2 (GEPIA2) and Human Protein Atlas (HPA) databases were utilized to verify the results. Furthermore, Gene Set Enrichment Analysis (GSEA) identified the potential key pathways that dominate cuproptosis in HCC. Results: Elevated SCO2, ATP7A, SLC25A3, COA6, TMEM199, ATP6AP1, LIPT1, DLAT, PDHA1, MTF1, ACP1, FDX2, NUBP2, CIAPIN1, ISCA2, NDOR1, ABCB6, CDKN2A, CDKN3, TPI1, and HSPA8 expression, as well as declined AOC1, FDX1, MT-CO1, and ACO1 expression were significantly emerged in HCC tumor tissues and were significantly associated with HCCs poor survival. The expressions of screened cuproptosis-related genes were prominently related to clinical features. GSEA analysis reported many key signaling pathways (such as natural killer cell mediated cytotoxicity, TCA cycle, glutathione metabolism, ATP-binding cassette (ABC) transporters, Notch signaling pathway, ErbB signaling pathway, and metabolism of xenobiotics by cytochrome p450) were differentially enriched in HCCs with varying degrees of cuproptosis-related genes expression. Conclusions: The twenty cuproptosis-related genes might be utilized as new candidate prognostic biomarkers for HCC.